2015
DOI: 10.1140/epjds/s13688-015-0040-6
|View full text |Cite
|
Sign up to set email alerts
|

High resolution population estimates from telecommunications data

Abstract: Spatial variations in the distribution and composition of populations inform urban development, health-risk analyses, disaster relief, and more. Despite the broad relevance and importance of such data, acquiring local census estimates in a timely and accurate manner is challenging because population counts can change rapidly, are often politically charged, and suffer from logistical and administrative challenges. These limitations necessitate the development of alternative or complementary approaches to popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
90
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(96 citation statements)
references
References 26 publications
2
90
1
2
Order By: Relevance
“…Researchers have established connections between the underlying population distribution obtained from census estimates with telecommunications data [19]. A recent study demonstrated that "presence" information (i.e., an estimate of the number of users in a certain space based on their last interaction with the mobile network) can provide better correlation with census data [7].…”
Section: B Mobile Phone Databases For Population Estimationmentioning
confidence: 99%
See 3 more Smart Citations
“…Researchers have established connections between the underlying population distribution obtained from census estimates with telecommunications data [19]. A recent study demonstrated that "presence" information (i.e., an estimate of the number of users in a certain space based on their last interaction with the mobile network) can provide better correlation with census data [7].…”
Section: B Mobile Phone Databases For Population Estimationmentioning
confidence: 99%
“…Spatial and temporal aggregation combined with unit-of-measure blurring are used for privacy and proprietary reasons [19]. Database entries are summarized next (see footnote §), including definitions of associated symbols.…”
Section: Riskmentioning
confidence: 99%
See 2 more Smart Citations
“…A literature review on the subject has shown that Remote Sensing and Geographic Information System as an alternative has been long recognized as a costeffective way of getting population information (Wang et al 2016, Greger 2015, Martin et al .2015, Jia et al 2014, Douglass et al 2015. In general, areal interpolation and statistical modeling methods have * Corresponding author been categorized in terms of their aim and required data.…”
Section: Introductionmentioning
confidence: 99%